2021
DOI: 10.3390/molecules26216547
|View full text |Cite
|
Sign up to set email alerts
|

Mangiferin and Hesperidin Transdermal Distribution and Permeability through the Skin from Solutions and Honeybush Extracts (Cyclopia sp.)—A Comparison Ex Vivo Study

Abstract: Polyphenolic compounds—mangiferin and hesperidin—are, among others, the most important secondary metabolites of African shrub Cyclopia sp. (honeybush). The aim of this study was to compare the percutaneous absorption of mangiferin and hesperidin from solutions (water, ethanol 50%, (v/v)) and extracts obtained from green and fermented honeybush (water, ethanol 50%, (v/v)). Research was performed with the Bronaugh cells, on human dorsal skin. The mangiferin and hesperidin distributions in skin layers (stratum co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 84 publications
(116 reference statements)
0
10
0
Order By: Relevance
“…In our study, the anti-aging potential of the flavonoids hesperidin and hesperetin and their carbohydrate components rutinose, and rhamnose were investigated. The transdermal distribution of hesperidin has already been demonstrated, so we focused on its biological activity during skin aging [ 11 ]. First, their ability to inhibit the activities of enzymes associated with skin aging, specifically hyaluronidase, collagenase, and elastase, which degrade the components of the ECM, was determined in the tube test.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, the anti-aging potential of the flavonoids hesperidin and hesperetin and their carbohydrate components rutinose, and rhamnose were investigated. The transdermal distribution of hesperidin has already been demonstrated, so we focused on its biological activity during skin aging [ 11 ]. First, their ability to inhibit the activities of enzymes associated with skin aging, specifically hyaluronidase, collagenase, and elastase, which degrade the components of the ECM, was determined in the tube test.…”
Section: Discussionmentioning
confidence: 99%
“…Transdermal distribution of hesperidin has also been demonstrated. The results of the study by Hering et al (2021) showed that hesperidin was able to cross the stratum corneum , the upper layer of the epidermis, and penetrate the deeper layers of the epidermis and dermis [ 11 ]. Although the bioavailability of hesperidin and hesperetin is relatively low, it can be increased by modifying a number of substances for topical application.…”
Section: Introductionmentioning
confidence: 99%
“…An infinite dose protocol in a flow‐through cell was applied, and it was observed that hesperidin permeated poorly from the extract, while a moderate to high ability to cross the membrane was seen in solutions of the isolated compound. The capacity of mangiferin to reach the acceptor fluid from the fermented honeybush extract was higher than from the green aerial parts extract after 24 h, showing that the extract composition modulates the behaviour of its various components [70].…”
Section: Plant Phenolics Permeation Profilementioning
confidence: 99%
“…The ex vivo experiments indicated that hesperidin penetrates the skin from water and ethanol solutions with higher efficiency than from honeybush extracts. In addition, hesperidin indicates a lack of ability to interact with skin macromolecules, but, being unbound, may be capable of protecting cells against UV radiation and oxidative stress [ 24 , 25 ]. Mangiferin, in contrast to hesperidin, from honeybush extracts has shown a greater ability to penetrate the skin [ 21 , 24 ] and exhibited an ability to interact with skin extracellular matrix (ECM) molecules, incompetently inhibiting elastase and collagenase activity [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, hesperidin indicates a lack of ability to interact with skin macromolecules, but, being unbound, may be capable of protecting cells against UV radiation and oxidative stress [ 24 , 25 ]. Mangiferin, in contrast to hesperidin, from honeybush extracts has shown a greater ability to penetrate the skin [ 21 , 24 ] and exhibited an ability to interact with skin extracellular matrix (ECM) molecules, incompetently inhibiting elastase and collagenase activity [ 21 ]. ECM compounds, such as collagen and elastin, are the structural and elasticity fibres of many organs and tissues [ 26 , 27 ], and they are also presented in abundant amounts among skin layers, where, with hyaluronic acid, they determine the skin functions [ 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%